Levels of Neurospecific Peptides, Neurotransmitters and Neuroreceptor Markers in the Serum of Children with Various Sensory Disorders, Mild Cognitive Impairments and Other Neuropathology - George A. Karkashadze; Leyla S. Namazova-Baranova; Leonid M. Yatsik; Olga B. Gordeeva; Elena A. Vishneva; Kamilla E. Efendieva; Elena V. Kaytukova; Natella V. Sukhanova; Natalia S. Sergienko; Julia V. Nesterova; Svetlana E. Kondratova; Madina T. Fatakhova; et al. (Педиатрическая фармакология)
Background. The role of recently discovered neurospecific peptides in the pathogenesis of acute and progressive neurologic disorders, their neuroprotective features, and possibilities to use them as markers for the course and prognosis of certain diseases have been actively studied in recent decades. However, neurospecific peptides are almost not studied in chronic residual diseases. In our study we measured the levels of neurospecific peptides and some other markers to achieve understanding of general neurophysiological trends in congenital and acquired chronic non-progressive brain pathology with reference to the selection of relevant groups — study objects. Objective. The aim of the study is to study patterns of neurospecific peptides, neurotransmitters and neuroreceptor markers distribution in the serum of children with various pathogenetic variants of chronic neuropathology. Methods. The study included children from 3 to 16 years old with different pathologies. The sample was divided into groups by pathology type: no sensory and neurological disorders, congenital sensory deficit due to mutation of genes expressed and not expressed in the brain, early acquired sensory deficit of multifactorial nature, congenital mild and severe organic disorders of central nervous system (CNS) in residual stage without baseline sensory deficit, acquired functional CNS disorders without baseline organic defect and sensory deficit. The following laboratory data (neurophysiological components) was studied: nerve growth factor, brain-derived neurotropic factor, neurotrophin-3, neurotrophin-4, neuregulin-1-beta-1, beta-secretase, sirtuin-1, synaptophysin, neuronal nitric oxide synthase, and anti-NR2 glutamate receptor antibodies. The parameters of cognitive activity, sense of vision, sense of smell, and acoustic sense were also evaluated. Results. The study included 274 participants. Neuropeptides and markers have shown a variable degree and range in the group spectrum of differences from normal levels. The most variable in the examined sample was NO-synthase, as well as levels of both neurotrophins, beta-secretase, and glutamate receptor marker. All visual deficits were associated with increased NO-synthase levels (p < 0.001). Neuroplasticity peptides (beta-secretase, neurotrophin-3 and 4) have been activated in all pathological conditions. Nerve growth factor and brain-derived neurotropic factor were specifically activated in mild organic CNS lesions (mild cognitive impairments), while neuregulin — in congenital genetically determined visual deficits. There was no specific activation of neuropeptides and NO-synthase level tended to decrease in cases of severe CNS lesions. Conclusion. The study results suggest that all types of early visual impairment are associated with increased physiological neuronal activity, and non-organic neurological functional disorders — mainly with increased physiological synaptic activity. General neuroplasticity processes were activated in all cases of visual deficits but more specific. However, more specific and well-studied processes were activated in mild organic CNS lesions, and neuroplasticity processes did not activate adequately in severe organic CNS lesions probably due to the limited neuronal and synaptic resources.